2005
DOI: 10.1007/s00428-005-1251-1
|View full text |Cite
|
Sign up to set email alerts
|

Pontosubicular apoptosis (“necrosis”) in human neonates with intrauterine growth retardation and placental infarction

Abstract: In a previous study of 37 autopsied stillbirths with non-dysmorphic intrauterine growth retardation (IUGR), 26 cases were associated with placental infarction, a morphologic marker of uteroplacental insufficiency. Nine of the 26 cases with both IUGR and placental infarction, where archival tissue was available, had grey matter ischaemic lesions that were subsequently identified as "pontosubicular necrosis". This lesion is now regarded as a localized form of apoptosis. A further eight third trimester stillbirth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…During labor, uterine contractions can further compromise placental blood flow and oxygen supply to the FGR fetus, thereby increasing the risk of an intrapartum hypoxic-ischemic event and subsequent brain injury (9). Several authors have also reported that FGR fetuses are not only at great risk of perinatal hypoxic ischemic events but also may be more susceptible to hypoxic-ischemic brain damage, compared with appropriate-for-GA (AGA) fetuses (9,10).…”
Section: F Etal Growth Restriction (Fgr)mentioning
confidence: 99%
“…During labor, uterine contractions can further compromise placental blood flow and oxygen supply to the FGR fetus, thereby increasing the risk of an intrapartum hypoxic-ischemic event and subsequent brain injury (9). Several authors have also reported that FGR fetuses are not only at great risk of perinatal hypoxic ischemic events but also may be more susceptible to hypoxic-ischemic brain damage, compared with appropriate-for-GA (AGA) fetuses (9,10).…”
Section: F Etal Growth Restriction (Fgr)mentioning
confidence: 99%
“…Large villous infarcts have been associated with ischemic CNS lesions in stillborns. 6,7 Finally, episodes of acute maternal hypotension related to cardiac arrest, amniotic fluid embolus, or septic shock are among the so-called ''sentinel events'' that can directly cause fetal brain injury.…”
Section: Maternal Circulatory Lesions Reduced Flow Large Vesselsmentioning
confidence: 99%
“…(2009) 9 suggested that some placental abnormalities found were associated with clinical causes of still birth, such as placental infarction and IUGR. Burke C, Globe G (2005) 10 suggested that apoptosis was strongly associated with IUGR and placental infarction. Regarding calcification in IUGR group it was found in 6 placenta and in control group in 2 placenta.…”
Section: Study Group Control Groupmentioning
confidence: 99%